Navigating Research Enthusiasm in Medical Students Towards Clinically Impactful Articles - Muhammad Abdul-Qadeer; Danish Ramesh; Samar Mahmood (University Library System, University of Pittsburgh, 2023)
Learning medical research is an integral part of the development of a holistic physician. Though, not all physicians become clinician-scientists, those who do become enjoy significant privileges over their clinician-only counterparts, mainly in terms of faster career progression and higher employability. Though, to produce more well-rounded clinician-scientists, academic physicians and medical scientists need to make themselves available and be willing to work with and mentor medical students. Besides, a curriculum reform is warranted where students should be encouraged to start learning and conducting research in their first year of medical school. To make the process even easier and help scale these ideas, students should be encouraged to replicate previous highly cited studies, as they can provide a walkthrough for students to follow, thereby necessitating lesser supervision while maintaining the clinical impact that can be made with their time and effort.